Vinculação e cultura emergente em jogos eletrônicos: análise midiática do ambiente da comunidade competitiva de Super Smash Bros. Melee - Schmitt, Augusto Salles (2019)
The current research has its objective in the investigation of which bonds are established between players of Super Smash Bros. Melee in competitive ambience. As such, we describe the playful activity and game through authors regarding the field of ludology, mainly through Jesper Juul’s Classic Game Model. Through the description of the game as an activity that creates symbolic and emergent values in different aspects of the events and tournaments of this community, we are enabled to identify cultural manifestations that can be analyzed by theories such as Norval Baitello’s and Harry Pross’ Cultural Semiotics, Image and Media studies. Through this theoretical lens we consider the human body as the key point of communication studies, as the body is present in both ends of any process of communication and bonding. The description of players gestures and media artifacts through Vilém Flusser’s communication theory enables us to form a structural description of our object to cathegorize and define the bonds we seek as objective. As such, it was observed that the activity of play of this video game as a process of communication enabled several bonds to be formed between players, and it also creates an ambience in which sociability is valued and sustained through cultural and symbolic values